Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD Negeri 75 Parepare - Nur Rahmatan Mursalin (Journal of Teaching dan Learning Research, 2022)
Students who study well will produce satisfactory learning outcomes and in accordance with expectations. The purpose of this study was to find out how the application of the snowball throwing type of cooperative learning model to improve students' social studies learning outcomes. The research subjects were teachers and students of class VB SD Negeri 75 Parepare, with a total of 18 students, consisting of 11 boys and 7 girls for 2 days. The method used is a quasi-experimental method using cycle I and cycle II. In the first cycle there are planning, implementation, observation and reflection. In cycle II, there are planning, implementation, observation and reflection combined with the development of Production, Communication, and Transportation Technology. The findings of this study indicate that the implementation of learning at the first cycle meeting has not succeeded in achieving the good category according to what has been determined. And student learning outcomes in cycle II have not met the demands of success indicators, namely 76% of students are able to master the learning material by getting a minimum score of 76. The findings of the third cycle showed student learning outcomes in general there was an increase in student participation in the class both individually and in groups as well as students' absorption of learning materials. The cooperative learning model can be a supporting literature to maximize student learning outcomes not only in social studies subjects. Furthermore, the discussion and implications will be discussed in more detail in this study.